2016
DOI: 10.1371/journal.pone.0151343
|View full text |Cite
|
Sign up to set email alerts
|

Topotecan Delivery to the Optic Nerve after Ophthalmic Artery Chemosurgery

Abstract: Extraocular retinoblastoma is a major challenge worldwide, especially in developing countries. Current treatment involves the administration of systemic chemotherapy combined with radiation, but there is a clear need for improvement of chemotherapy bioavailability in the optic nerve. Our aim was to study the ophthalmic artery chemosurgery (OAC) local route for drug delivery assessing ocular and optic nerve exposure to chemotherapy and to compare it to exposure after intravenous infusion (IV) of the same dose i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 42 publications
0
21
0
Order By: Relevance
“…The controversy regarding the rate of metastases following first line intra-arterial versus intravenous chemotherapy for advanced disease clashes with biases linked to the fact that these two administration routes influence the ratio of CNS versus non-CNS dissemination (Brennan et al, 2015). Neoadjuvant systemic chemotherapy may offer a less favorable coverage in patients with high risk for CNS involvement when compared to the unmatched chemotherapeutic optic nerve concentration achieved by intra-arterial drug delivery (Taich et al, 2016), while intravenous chemotherapy may be more efficient against distant minimally disseminated disease. Although the end result in terms of survival remains unknown to date, patient survival following the introduction of first line intra-arterial chemotherapy appears, however, unimpaired compared to previous treatment regimens, with no increase in the metastasis rate, ranging between 2 and 2.5% (Funes et al, 2018) and death rate from metastatic disease around 1% (Abramson et al, 2017b).…”
Section: Influence Of Conservative Retinoblastoma Treatment In the Ocmentioning
confidence: 99%
“…The controversy regarding the rate of metastases following first line intra-arterial versus intravenous chemotherapy for advanced disease clashes with biases linked to the fact that these two administration routes influence the ratio of CNS versus non-CNS dissemination (Brennan et al, 2015). Neoadjuvant systemic chemotherapy may offer a less favorable coverage in patients with high risk for CNS involvement when compared to the unmatched chemotherapeutic optic nerve concentration achieved by intra-arterial drug delivery (Taich et al, 2016), while intravenous chemotherapy may be more efficient against distant minimally disseminated disease. Although the end result in terms of survival remains unknown to date, patient survival following the introduction of first line intra-arterial chemotherapy appears, however, unimpaired compared to previous treatment regimens, with no increase in the metastasis rate, ranging between 2 and 2.5% (Funes et al, 2018) and death rate from metastatic disease around 1% (Abramson et al, 2017b).…”
Section: Influence Of Conservative Retinoblastoma Treatment In the Ocmentioning
confidence: 99%
“…However, the only survivor in the initial diagnosis group had positive MDD in the CSF at diagnosis, suggesting that intensive treatments may rescue these patients, as we reported in cases with high‐risk pathology features . Intra‐arterial chemotherapy may be considered as a way to achieve higher chemotherapy exposure to the optic nerve compared to systemic chemotherapy . Since a high proportion of our patients have MDD, in case intra‐arterial is used to treat orbital retinoblastoma, it should be combined with other systemic and CNS‐directed therapies.…”
Section: Discussionmentioning
confidence: 72%
“…11 Intra-arterial chemotherapy may be considered as a way to achieve higher chemotherapy exposure to the optic nerve compared to systemic chemotherapy. 15,16 Since a high proportion of our patients have MDD, in case intra-arterial is used to treat orbital retinoblastoma, it should be combined with other systemic and CNS-directed therapies.…”
Section: Discussionmentioning
confidence: 99%
“…The results from two previous studies were used as a background for this strategy. First, the 80‐fold higher exposure attained in the optic nerve, retina, and vitreous with IAC compared to the same intravenous dose in an animal model would be critical to obtain a higher chemotherapy exposure . The marked response to treatment in this child cannot be explained only by direct exposure of the affected tissues after IAC.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, systemic chemotherapy fails to achieve effective drug levels in critical tissues. Preclinical studies have shown a significantly higher chemotherapy exposure in the optic nerve (the major source for CNS dissemination) after intra‐arterial chemotherapy (IAC) compared to standard IV infusion; however, most cases with CNS invasion have extension through the chiasm, which is not supplied by the ophthalmic artery. Thus, if this modality was to be considered for treating these cases, an alternative route of drug delivery to the optic nerve and chiasm should be developed.…”
Section: Introductionmentioning
confidence: 99%